Haemoptysis as the sole presenting symptom of dissection of the aorta. Issue 5 (May 1989) - Guidetti, A S; Pik, A; Peer, A; Shikiar, S; Ben-Yaakov, D
Abstract : A 75 year old man who had had haemoptysis for 24 hours was found to have his left lower lobe compressed by a dissection of the aorta, which was otherwise symptomless.